1985
DOI: 10.1042/bj2320191
|View full text |Cite
|
Sign up to set email alerts
|

Pertussis toxin substrate is a guanosine 5′-[β-thio]diphosphate-, N-ethylmaleimide-, Mg2+- and temperature-sensitive GTP-binding protein

Abstract: We compared the effects of guanine nucleotides and Mg2+ on ADP-ribosylation of rat brain and liver membrane proteins catalysed by Bordetella pertussis toxin (IAP) and cholera toxin (CT). Labelling of proteins in the presence of [alpha-32P]NAD+, ATP and CT required GTP or guanosine 5'-[gamma-thio]triphosphate (GTP [S]). In contrast, labelling of one (liver) or two (brain) polypeptides by IAP was enhanced by guanosine 5'-[beta-thio]diphosphate (GDP[S]) or GTP, but was blocked by GTP[S] or guanosine 5'-[beta, gam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

1987
1987
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 32 publications
1
17
0
Order By: Relevance
“…As the effect of GH on the ability of PIA to inhibit the lipolytic system was retained in isolated membranes, it allowed further dissection of the basis of the GH effect. Pertussis toxin elicits the ADP-ribosylation of the undissociated G i heterotrimer (Tsai et al 1984, Wong et al 1985; interaction of G i with the activated receptor causes dissociation of G i into the subunit and the subunit with a concomitant decrease in pertussis toxin-catalysed ADP-ribosylation. Thus pertussis toxin-catalysed ADPribosylation along with determination of the total amount of G i by immunoblotting can provide an indication of the proportion of the heterotrimer that has dissociated into and subunits.…”
Section: Tablementioning
confidence: 99%
“…As the effect of GH on the ability of PIA to inhibit the lipolytic system was retained in isolated membranes, it allowed further dissection of the basis of the GH effect. Pertussis toxin elicits the ADP-ribosylation of the undissociated G i heterotrimer (Tsai et al 1984, Wong et al 1985; interaction of G i with the activated receptor causes dissociation of G i into the subunit and the subunit with a concomitant decrease in pertussis toxin-catalysed ADP-ribosylation. Thus pertussis toxin-catalysed ADPribosylation along with determination of the total amount of G i by immunoblotting can provide an indication of the proportion of the heterotrimer that has dissociated into and subunits.…”
Section: Tablementioning
confidence: 99%
“…It has been demonstrated that IAP can catalyze the transfer of ADP-ribose from N A D to a subunits of Gi and Go, namely Cia and Goa (Katada & Ui 1982;Katada et al 1986). These results suggest that IAP preferably catalyzes the transfer of ADP-ribose from N A D to G i / G o when G proteins are taking the undissociated or GDP-bound form (Codina et al 1984;Wong et al 1985;Katada ef al. Then, the mixture of a subunits of Gi and G o was quantitated as a whole.…”
Section: Discussionmentioning
confidence: 99%
“…Then, the mixture of a subunits of Gi and G o was quantitated as a whole. Perhaps GTP is converted into GDP during the incubation, which might explain why IAP-catalyzed ADP-ribosylation of G i / G o is enhanced by addition of GTP even in the presence of MgCI, (Wong et al 1985) 2). 1 lyzed by IAP was enhanced by GTP and CDPpS both in the absence and presence of MgCI2, whereas, in the case of IAP-mediated ADP-ribosylation with GTPyS and GPP(NH)p, 32P-incorporation was enhanced in the absence of MgC1, but markedly reduced in the presence of 10 m M MgCI?.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cells were incubated with pertussis toxin (OS-1 gg/ml) for a total of 1 h. After 30 min of incubation the quinZAM was added as already described. Pertussis toxin was preactivated by incubating appropriate portions in 50 mM dithiothreitol for 1 h at 25°C [20].…”
Section: Quin2 Loading and Measurement Of [Cd']imentioning
confidence: 99%